Anatomical and Histologycal Study on Digestive Organs of Tree Shrew (Tupaia javanica) - Bahartin, Widya; Nisa, Laila Ainun; Luthfi, M. Ja’far (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Squirrels are members of the class of mammals which are also included in the Scandentian order. This study aims to determine the anatomical structure and histology of the digestive organs of the squirrel kekes (Tupaia javanica). The research consisted of the stage of making histology slides of the digestive organs of squirrel kekes using the paraffin method and the Hematoxylin-Eosin staining method. The digestive organs in this study consist of the esophagus, stomach, small intestine, large intestine, and liver. Histological observations show that the organs of the esophagus (esophagus), stomach, small intestine, and large intestine are found in some of the same tissues, among others, epithelium tissue, lamina propria, mucosa, submucosa, serosa and adipose. While the liver is found in several tissues including the hepatic sinusoid, central vein, portal vein, hepatic arteries and lymphatic vessels.